(untitled) (Journal of Entomological and Acarological Research, 2024)
Pentatomid bugs, commonly known as stink bugs, are typically herbivorous insects known for their piercing-sucking feeding habits on crops and wild plants. Among these stink bugs, Spermatodes variolosus (Walker, 1867) stands out as the smallest species, measuring 2.6-2.9 mm, and is also known to be phytophagous. In this study, we report the presence of seven species from six different genera of stink bugs in the rice fields of Cooch Behar, West Bengal. Notably, this research marks the first documented occurrence of Spermatodes variolosus (Walker, 1867) in the rice ecosystem of India, raising concerns about its potential pest status. Furthermore, this study includes taxonomic keys for the six genera identified.